The Influence of Knowledge Economy Development on Competitiveness of Southeastern European Countries - Krstić, Bojan D; Stanišić, Tanja S (Industrija, 2013)
The purpose of this research is to analyze the influence of knowledge as a vital development resource on competitiveness of Southeastern Europe (SEE) countries. The aim is to identify correlation among the achieved knowledge economy development level measured by the KEI (Knowledge Economy Index) and competitiveness level measured by the GCI (Global Competitiveness Index) in the SEE countries. The study is realized by using descriptive statistics, correlation, regression and comparative analysis. Structurally, the paper is composed of the following parts: analysis of the competitiveness of SEE countries according to the GCI and the KEI, as well as according to the pillars within the KEI, examination of interdependence GCI and KEI and examination of the impact of the pillar within the KEI on GCI in SEE countries. Research results indicate that there is a weak positive correlation between the GCI and KEI. The results of this study provide recommendations to development policy makers in SEE countries.
Keywords: SEE countries; Knowledge; Economy; Competition